PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI - Nur Azijah, Siti; Rahmawati, Rita; Rusliandy; Wahyudin, Cecep; Anak Lydon, Novel (Jurnal Governansi, 2024)
A leader's behavior can significantly impact civil servant performance because improving civil servant performance depends on a leader's expertise. This research aims to determine the influence of leadership on civil servant performance. This research was conducted at the Bogor Regency BPN office. The research methods used are descriptive and associative with a quantitative approach. The sample determination technique uses random sampling based on the Slovin formula to obtain a sample size of 135 respondents from a total population of 204. The data collection technique is based on observation, questionnaires, and interviews. The method for analyzing research data applies the Weight Mean Score formula, then continues to use hypothesis testing, namely the t-test and termination coefficient. The research results show that leadership has a significant influence on civil servant performance. Based on the t-test, it is known that the significance value is 0.000<0.05, and the calculated t-value of 4.407 is greater than the t-table value of 1.978. The level of influence of leadership variables on civil servant performance is 44.8%, and other factors influence other percentages. In the leadership variable, the highest dimension in income, the average score is in the achievement-oriented indicator in work with an average score of 4.2, and the lowest dimension is in the directive, supportive, and participative indicator with an average score of 4 with suitable criteria. Meanwhile, the highest dimension of the civil servant performance variable is the quality of work dimension, with an average score of 4.2; it proves that the quality of employee performance at the BPN Office is good, and the lowest dimension is the dimension of work knowledge and creativity, with an average score of 4 with suitable criteria.